Māttrathān khō̜mūn Krasūang Rǣngngān pī 2553 : mattrathān khō̜mūn khon, mattrathān khō̜mūn sathān prakō̜pkān, mattrathān khō̜mūn sawatdikān læ phonprayōt tō̜pthǣn (Krasūang Rǣngngān, 2010)
On data of the Ministry of Labour, Thailand, on persons, establishments, and welfares.